"Different Strolls, Different Worlds? Gentrification and its Impact on Outdoor Sex Work". (19th November 2020) - Oselin, Sharon S; Hail-Jares, Katie; Kushida, Melanie
Abstract: Research reveals mixed findings regarding gentrification's effects on longtime residents and legal small businesses. There is only minimal examination of the ways in which urban redevelopment impacts illicit outdoor marketplaces, and the studies that do rarely employ a comparative analysis or focus on individual perceptions regarding such changes. Using the case of street-based sex work, this study illuminates how workers in the outdoor trade assess changing work conditions and establishes that such evaluations color workers' decision-making. We draw on interviews with 51 sex workers of color who are familiar with two divergent sex work "strolls" in Washington, DC. Our findings suggest that participants perceive gentrification as a multifaceted phenomenon that reconfigures their work by altering social support, environmental conditions, and competition, changes which ultimately inform where they ply their trade. This research shows that individuals in illicit outdoor markets consider the ramifications of urban redevelopment on their work and make strategic decisions that have implications for their emotional, physical, and financial well-being.